1992
DOI: 10.1099/0022-1317-73-8-2093
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetection of the proteins encoded by grapevine chrome mosaic nepovirus RNA2

Abstract: Fragments of the putative non-structural proteins (44K and 46K) encoded by RNA2 of grapevine chrome mosaic nepovirus (GCMV) were expressed as fusion proteins in Escherichia coli and used to raise specific antisera. All three proteins encoded by GCMV RNA2 (viral coat protein, and the 44K and 46K proteins) were detected by immunoblotting in subcellular fractions prepared from the leaves of infected Chenopodium quinoa plants, confirming a previously proposed model of the GCMV RNA2-encoded polyprotein. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…In general all movement proteins, or those proteins presumed to be so, including those of nepo-and comoviruses described to date, have been shown to be associated with these fractions (Demangeat et al, 1992;Hibrand et al, 1992;Shanks et al, 1989;Wellink et al, 1987). However, according to our data, the G F L V P38 protein is also highly cytosolic since it is found in large quantities in the S-30 soluble protein fraction.…”
Section: Subcellular Localization Of the P38 Proteinmentioning
confidence: 44%
See 1 more Smart Citation
“…In general all movement proteins, or those proteins presumed to be so, including those of nepo-and comoviruses described to date, have been shown to be associated with these fractions (Demangeat et al, 1992;Hibrand et al, 1992;Shanks et al, 1989;Wellink et al, 1987). However, according to our data, the G F L V P38 protein is also highly cytosolic since it is found in large quantities in the S-30 soluble protein fraction.…”
Section: Subcellular Localization Of the P38 Proteinmentioning
confidence: 44%
“…grapevine chrome mosaic virus (GCMV) 46K protein (Hibrand et al, 1992), tomato black ring virus (TBRV) 46K protein (Demangeat et al, 1992) and TomRSV 45K protein (Wieczorek & Sanfagon, 1993)] and comoviruses [CPMV 48K protein (Wellink et al, 1987) and red clover mottle virus (RCMV) 43K protein (Shanks et al, 1989)]. Many of the aforesaid proteins, some of which have been shown to be viral movement proteins, do not accumulate in vivo late in infection (Demangeat et al, 1992;Hibrand et al, 1992). In addition, CPMV 48K protein displays low stability and is almost completely degraded after 8 h of pulse-chase (Rezelman et al, 1989).…”
Section: Total Proteinsmentioning
confidence: 99%
“…The role served by this protein remains unknown but the amino acid triplet ' LPL' which Koonin et al (1991) implicated with virion movement within plants occurred at amino acid positions 63 to 65 in the SLRSV-H 26-6K coding sequence and a movement function for the protein coded in that region by SLRSV-H would accord with the experiences or suggestions of others [viz. CPMV (Wellink et al, 1987;Wellink & Van Kammen, 1989), TBRV (Hibrand et al, 1992;Demangeat et al, 1992) or other nepoviruses (Meyer et al, 1986;Brault et al, 1989;Rott et al, 1991)]. Nevertheless, comparisons between the 26.6K polypeptide of SLRSV-H and the 58/48K polypeptide of CPMV, the 30K protein of tobacco mosaic virus (Atabekov & Dorokhov, 1984;Meshi et al, 1987) or the region upstream of the coat protein coding sequences in ArMV, GCMV, GFLV, RRV, TBRV or TomRSV showed no unexpected affinities.…”
Section: Tbrv-smentioning
confidence: 99%
“…If this is the case, it would be facilitated by coordinate expression of the movement and coat proteins. The steady-state levels of the putative movement proteins from two other nepovirus have been reported to be transient in infected plants and it was thus concluded that the proteins were unstable (Demangeat et al, 1992;Hibrand et al, 1992). In contrast, the grapevine fanleaf nepovirus movement protein, which is present at late stages of infection of protoplasts and whole plants, is found mainly in the cytoplasmic fraction and was therefore suggested to be stable (Ritzenthaler et al, 1995).…”
mentioning
confidence: 99%